The effect of the clinical pharmacist in minimizing drug-related problems and related costs in the intensive care unit in Turkey: A non-randomized controlled study - AYHAN, YUNUS EMRE; KARAKURT, SAİT; SANCAR, MESUT (My University, 2022)
What is known and objective:Drug-related problems (DRPs) are common inhospitalized patients in intensive care unit (ICU). The aim of the study is to reduceDRPs and associated costs with clinical pharmacist's (CP) recommendations.Methods:The study is a prospective, non-randomized controlled study conducted inthe ICU for a total of 6 months (1 January 2021–30 June 2021) in 2-month con-trol, 2-month study, and 2-month control periods. Patients who were hospitalizedfor more than 24 h and used more than one medication were included in thestudy. The PCNE V9.1 Classification system was used in the classification ofDRPs. During the intervention period, CP recommendations for DRPs wereproposed to the healthcare team.Results and discussion:A total of 146 patients were included in the study. A total of1061 DRPs from all periods were detected. The most common causes of DRPs werepotential drug–drug interactions (31.76%), high dose (12.44%), and dose timinginstruction errors (9.24%). For 347 DRPs identified during the study period, 259 inter-ventions (74.63%) were recommended, and 238 (91.89%) were accepted by physi-cians. Interventions were mostly made as interrupting/discontinuing the drug(28.02%), changing the dose (25.27%), changing the instructions for use (20.32%),and starting a new drug (15.93%). Cost savings were achieved with CP recommenda-tions applied.What is new and conclusion:The CP's recommendations were highly accepted bythe healthcare team. With the CP's participation in routine patient rounds in thehealthcare team of the ICU, drug-related costs would also decrease.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; clinical pharmacist; cost saving; drug-related problems; intensive care unit; PCNE; IMPACT; INTERVENTIONS; THERAPY; EVENTS; ROUNDS; clinical pharmacist; cost saving; drug-related problems; intensive care unit; PCNE